HUBUNGAN RESPONSE TIME PERAWAT DENGAN KEPUASAN KELUARGA PASIEN DI INSTALANSI GAWAT DARURAT (IGD) RSUD Dr. PIRNGADI MEDAN TAHUN 2016 - Marlisa Marlisa (Poltekkes Kemenkes Medan, 2017)
Family statisfaction is determined by a good response time. The objective of this research is to investigate the correlation between the nurses’s response time in giving service and family statisfaction at Emergency Unit of RSUD Dr.Pirngadi Medan This research use th correlational descriptive method. The population of this research consisted of 597 patient. Yhe sample of the research consisted of 42. They were colleted through stopwacth/handphone that have a stopwatch to caculate the response time and questionnsire consisting of 20 questions about family statisfiction of patient.The result of the research show that nurses’response time at Emergency Unit RSUD Dr.Pirngadi Medan was a past’s response time.In addition, the family of patients were statisfied with the service at Emergency Unit of RSUD Dr.Pirngadi Medan. There was a corelation between the nurses’s response time in giving service and the family statisfaction at Emergency Unit of RSUD Dr. Pirngadi of medan as indicate by the p.value= 0.02 and the correlation coeficient value=0.01